The interpretation of dreams - Freud, Sigmund, 1856-1939.; Strachey, James (New York : Perseus Books Group, 2010)
Whether we love or hate Sigmund Freud, we all have to admit that he revolutionized the way we think about ourselves. Much of this revolution can be traced to The Interpretation of Dreams, the turn-of-the-century tour de force that outlined his theory of unconscious forces in the context of dream analysis. Introducing the id, the superego, and their problem child, the ego, Freud advanced scientific understanding of the mind immeasurably by exposing motivations normally invisible to our consciousness.
The scientific literature dealing with the problems of dreams -- The method of interpreting dreams : an analysis of a specimen dream -- A dream is the fulfilment of a wish -- Distortion in dreams -- The material and sources of dreams -- The dream-work -- The psychology of the dream-processes.
Includes bibliographical references and index.
Print version record.
Keywords: Dreams; Psychoanalysis